Tensile Properties of Luffa Acutangula Reinforced Polymer Composite - Indor, Christopher Joyle; Nicholas Kuan, Hoo Tien; Yeo, Freddy Kuok San; Afiq, Mohd Khairul (International Journal of Integrated Engineering, 2023)
In recent years, there has been a growing trend in the popularity of natural fiber-reinforced polymer composites (NFRPC). Numerous researchers have put forward various alternatives to synthetic fibers. Luffa is one of the many natural fibers can be integrated into NFRPCs. Luffa with its unique interconnecting branch (mat/mesh) is suitable for NFRPCs. In this study, luffa reinforced high-density polyethylene (Luffa/HDPE) composite was fabricated using compression molding machine. In the preparation of the fiber, Luffa were cylindrically cut-out and opened into sheets form. The fiber was then laminated with high-density polyethylene (HDPE) film using compression molding method. The proposed fabricated composite consisting of a fiber volume fraction (FVF) of 7%, 14%, 21%, 27% and 30%. Tensile properties of the Luffa/HDPE composite were determined. SEM was used to study the interlamination and delamination of the composite. Tensile test shows that the increase of FVF enhanced the tensile strength of Luffa/HDPE composite. Tensile strength has gradually increased from 7 % to 21 % FVF. Though, tensile strength declines after 21% FVF.